Proposals for mitigation of pollutant emissions from aircraft: application to Lisbon airport - Ribeiro, Joana André Matias; Macário, Rosário; Reis, Vasco (Transportes, 2011)
Proposals for mitigation of pollutant emissions from aircraft: application to Lisbon airport